A review of the role of sebum in the mechanism of acne pathogenesis. (29th May 2017) - Li, Xinchao; He, Congfen; Chen, Zhou; Zhou, Cheng; Gan, Yao; Jia, Yan
Summary: Acne is one of the most common skin disorders, and its occurrence is closely related to many factors, including sebum secretion, hormone levels, bacterial infection, and inflammatory reactions. Among these, changes in sebum secretion are believed to be one important factor of acne. Increased sebum secretion can induce acne occurrence, and increasing evidence indicates sebum component changes are also strongly related to acne occurrence. Recently, developments in lipidomics have provided effective lipid analysis methods. These can help elucidate the effects of different types of sebum on acne occurrence and provide a theoretical basis for research on the mechanisms of acne pathogenesis and treatment.